Dynamic Arterial Elastance as a Ventriculo-Arterial Coupling Index: An Experimental Animal Study - Monge García, Manuel Ignacio; Jian, Zhongping; Hatib, Feras; Settels, Jos J.; Cecconi, Maurizio; Pinsky, Michael R. (Frontiers in Physiology, 2020)
Dynamic arterial elastance (Eadyn), the ratio between arterial pulse pressure and stroke volume changes during respiration, has been postulated as an index of the coupling between the left ventricle (LV) and the arterial system. We aimed to confirm this hypothesis using the gold-standard for defining LV contractility, afterload, and evaluating ventricular-arterial (VA) coupling and LV efficiency during different loading and contractile experimental conditions. Twelve Yorkshire healthy female pigs submitted to three consecutive stages with two opposite interventions each: changes in afterload (phenylephrine/nitroprusside), preload (bleeding/fluid bolus), and contractility (esmolol/dobutamine). LV pressure-volume data was obtained with a conductance catheter, and arterial pressures were measured via a fluid-filled catheter in the proximal aorta and the radial artery. End-systolic elastance (Ees), a load-independent index of myocardial contractility, was calculated during an inferior vena cava occlusion. Effective arterial elastance (Ea, an index of LV afterload) was calculated as LV end-systolic pressure/stroke volume. VA coupling was defined as the ratio Ea/Ees. LV efficiency (LVeff) was defined as the ratio between stroke work and the LV pressure-volume area. Eadyn was calculated as the ratio between the aortic pulse pressure variation (PPV) and conductance-derived stroke volume variation (SVV). A linear mixed model was used for evaluating the relationship between Ees, Ea, VA coupling, LVeff with Eadyn. Eadyn was inversely related to VA coupling and directly to LVeff. The higher the Eadyn, the higher the LVeff and the lower the VA coupling. Thus, Eadyn, an easily measured parameter at the bedside, may be of clinical relevance for hemodynamic assessment of the unstable patient.